Hubungan Kecemasan dengan Kecendrungan Psikosomatis Remaja Pada Pandemi Covid 19 Di Kota Palembang - Delia Yusfarani (Universitas Batanghari Jambi, 2021)
Psychosomatic will attack individuals who respond to environmental conditions with excessive anxiety. COVID-19 is an infectious disease that comes suddenly so that people are not ready to face it both physically and psychologically, among the psychological conditions experienced by the community is a sense of anxiety. This anxiety is also experienced by teenagers because adolescence can be said to be an unstable age in the face of unexpected conditions. This study aims to determine the relationship between anxiety and psychosomatic tendencies in adolescents during the COVID-19 pandemic in Palembang City. The method used is descriptive quantitative with a total of 245 teenagers as respondents using a purposive random sampling technique. Data collection used the Instrument Depression Anxiety Stress Scales (DASS 42) which were distributed online. Bivariate analysis was performed using chi-square and descriptive analysis using the Statistical Product and Service Solutions (SPSS) program. The results showed that there were 50.20% more adolescents in the age group 15-19 years old than the 20-24 years age group as much as 49,80%, 51,43% more than boys as much as 33.87%, adolescents are never anxious as much as 124 (50,61%) more than adolescents anxious sometimes as much as 84 (34,29%), often anxious as much as 29 (11,84%), and very often anxious as much as 8 (3,26%), 142 (57,96%) more psychosomatic tendencies than 103 (42,04%) psychosomatic tendencies, and there is a significant relationship between anxiety and psychosomatic tendencies (p-value 0,036) in adolescents during the COVID pandemic. -19 in Palembang City in 2020.